2008
DOI: 10.1051/gse:2008019
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of QTL for age at puberty in gilts using a large intercross F2population between White Duroc times Erhualian

Abstract: -Puberty is a fundamental development process experienced by all reproductively competent adults, yet the specific factors regulating age at puberty remain elusive in pigs. In this study, we performed a genome scan to identify quantitative trait loci (QTL) affecting age at puberty in gilts using a White Duroc · Erhualian intercross. A total of 183 microsatellites covering 19 porcine chromosomes were genotyped in 454 F 2 gilts and their parents and grandparents in the White Duroc · Erhualian intercross. A linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Likewise a QTL for weight of ovary was also described in a Meishan–White composite population between 116 and 137 cM on SSC8 (Rohrer et al, 1999). An age at puberty study using a White Duroc–Erhualian population detected a peak at 77 cM on SSC8 using a 5% chromosome-wide threshold, but a secondary peak just below the threshold was notable at approximately 125 cM within the region of HPSE (Yang et al, 2008). It is also worth noting that Buske et al (2006) compiled several fertility-related QTL studies and found a predominant clustering of QTL across SSC8 for reproductive traits in swine.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise a QTL for weight of ovary was also described in a Meishan–White composite population between 116 and 137 cM on SSC8 (Rohrer et al, 1999). An age at puberty study using a White Duroc–Erhualian population detected a peak at 77 cM on SSC8 using a 5% chromosome-wide threshold, but a secondary peak just below the threshold was notable at approximately 125 cM within the region of HPSE (Yang et al, 2008). It is also worth noting that Buske et al (2006) compiled several fertility-related QTL studies and found a predominant clustering of QTL across SSC8 for reproductive traits in swine.…”
Section: Discussionmentioning
confidence: 99%
“…A three-generation White Duroc×Erhualian F 2 resource population was established as described previously [13]. In short, two White Duroc boars were mated to 17 Erhualian sows as founders.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was extracted from swine ear tissues using a standard phenol-chloroform method. The DNA samples were then quantified using a Nanodrop 1,000 spectrophotometer (Thermo Scientific, Waltham, MA, USA) and diluted to a concentration of 50 ng/μL in a 96-well plate as previously described [13]. A total of 1,020 individuals (19 F 0 , 68 F 1 , and 933 F 2 ) were genotyped using the Illumina PorcineSNP60 BeadChip (62,163 SNPs) according to the manufacturer's protocols.…”
Section: Dna Collection and Genotypingmentioning
confidence: 99%